Performance and Quality Comparison of Movie Alignment Software for Cryogenic Electron Microscopy - Střelák, David; Marchán, Daniel; Carazo, José María; S Sorzano, Carlos O (Micromachines, 2023)
Cryogenic electron microscopy (Cryo-EM) has been established as one of the key players in structural biology. It can reconstruct a 3D model of a sample at a near-atomic resolution. With the increasing number of facilities, faster microscopes, and new imaging techniques, there is a growing demand for algorithms and programs able to process the so-called movie data produced by the microscopes in real time while preserving a high resolution and maximal information. In this article, we conduct a comparative analysis of the quality and performance of the most commonly used software for movie alignment. More precisely, we compare the most recent versions of FlexAlign (Xmipp v3.23.03), MotionCor2 (v1.6.4), Relion MotionCor (v4.0-beta), Warp (v1.0.9), and CryoSPARC (v4.0.3). We tested the quality of the alignment using generated phantom data, as well as real datasets, comparing the alignment precision, power spectra density, and performance scaling of each program.
Keywords: FlexAlign; MotionCor2; Warp; performance; Relion MotionCor; CryoSPARC; movie alignment; Cryo-EM